On the Conceptual Basis of the English Adjectival Category - Marina Antonova (National Research University Higher School of Economics, 2015)
The paper focuses on the cognitive foundation of English adjectives that denote mental characteristics of human beings. Several cognitive models have been advanced in an attempt to account for the semantic structure underlying the lexical category in question. After reviewing these models, a method for determining which of them most accurately captures the "cognitive reality" of English adjectival "deep structure" is proposed. The paper concludes with arguments for the inclusion of additional "motion attributes" to Lakoff's ICM (1987), namely, "guide's support" and "speed".